2007
DOI: 10.1063/1.2430404
|View full text |Cite
|
Sign up to set email alerts
|

Transmission measurement at 10.6μm of Te2As3Se5 rib waveguides on As2S3 substrate

Abstract: The feasibility of chalcogenide rib waveguides working at λ = 10.6µm has been demonstrated. The waveguides comprised a several microns thick Te 2 As 3 Se 5 film deposited by thermal evaporation on a polished As 2 S 3 glass substrate and further etched by physical etching in Ar or CF 4 /O 2 atmosphere. Output images at 10.6µm and some propagation losses roughly estimated at 10dB/cm proved that the obtained structures behaved as channel waveguides with a good lateral confinement of the light. The work opens the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Although the SOI waveguides are relatively large we believe that sub dB/cm losses can be achieved by using even smaller structures such as for example LOCOS waveguides [26]. The propagation loss demonstrated here is also much lower than losses previously reported in the literature for other MIR waveguides [14,27,28].…”
Section: Resultsmentioning
confidence: 52%
“…Although the SOI waveguides are relatively large we believe that sub dB/cm losses can be achieved by using even smaller structures such as for example LOCOS waveguides [26]. The propagation loss demonstrated here is also much lower than losses previously reported in the literature for other MIR waveguides [14,27,28].…”
Section: Resultsmentioning
confidence: 52%
“…Due to the tellurium weight, glasses exclusively based on this heavy element are very exciting materials for far infrared applications. Driven by the Darwin mission [9] of the European Space Agency (ESA) as well as a mid-infrared sensing technology [10][11][12][13], an active research is currently conducted on new compositions that could be drawn into optical fiber. Within this framework, it has been recently demonstrated that telluride glasses with high stability and favourable optical properties could be fabricated either by alloying with Ge and Sb [14], Ge and Ga [15], Ge and I [16] or Ge and As [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In two previous studies, Labadie et al (2006b) and Vigreux-Bercovici et al (2007) presented evidence of the ability of Arsenic-SulfideSelenium (As-S-Se) structures to produce an efficient confinement of infrared radiation at λ = 10.6 μm. Hô et al (2006) demonstrated the fabrication of single-mode channel waveguides using multi-layer deposition of arsenic-based thin films followed by laser writing (Efimov et al 2001) to provide the lateral confinement of the field.…”
Section: Fabrication Of the Y-junctionmentioning
confidence: 99%